A contextual process: Understandings of transitional justice in Rwanda - Palmer, NF (2013)
This thesis examines the practices of international, national, and localised criminal courts in post-genocide Rwanda. It argues that, although the courts are compatible in law, an interpretive cultural analysis shows that they have often competed with one another. The research draws on interviews conducted with judges, lawyers, and a group of witnesses and suspects from the United Nations International Criminal Tribunal for Rwanda (ICTR), the national Rwandan courts, and the gacaca community courts. The courts’ judges and lawyers have interpreted Rwanda’s transitional justice processes very differently. The ICTR has been principally concerned with developing international criminal case law. The national courts purport to have focused on domestic legal reform, while personnel inside gacaca view these local courts as having provided an account of the events and causes of the genocide. This thesis argues that the different interpretations offered within Rwanda’s post-genocide courts illuminate divergent legal cultures inside the institutions, leading to failures in effective cooperation and evidence gathering. The courts have pursued diverse means to try to establish their legitimate authority. However, among a group of Rwandan citizens, the practices of one court were routinely used as the basis to criticise the actions of the others, raising challenges for the legitimacy of transitional justice in Rwanda. The potential for similar competition between domestic and international justice processes is apparent in the current practice of the International Criminal Court (ICC). However, this competition can be mitigated through more effective communication between different justice systems which respond to the needs of the affected populations, fostering a legal culture of complementarity.